Differential rail‐to‐rail voltage‐controlled quadrature ring oscillator for low‐power implantable transceivers. Issue 22 (1st October 2014) - Moradi, A.; Sawan, M.
Abstract : A new low‐power rail‐to‐rail voltage‐controlled quadrature oscillator is presented. This oscillator was implemented to provide the frequency deviation of frequency‐shift‐keying (FSK) modulation in implantable radio‐frequency (RF) transceivers. The quadrature oscillator circuit generates differential in‐phase and quadrature‐phase ( I and Q ) signals in a two‐stage ring configuration. The proposed structure of delay cells and the start‐up circuit were implemented using IBM 130 nm CMOS technology. The frequency can be tuned between 300 kHz and 11.57 MHz by varying the supply voltage from 0.35 to 0.9 V. An average current of 5.5 µA (2.5 µW) was consumed to generate rail‐to‐rail differential quadrature signals with a frequency of 2 MHz as the target operating point dedicated to low‐power implantable transceivers.